Performance Study of Intermittent Heating Mode Combining Air-Source Heat Pump with Radiator in Hot Summer and Cold Winter Zones of China - Mingjing Fan; Haifeng Cheng; Mengting Nian; Shiqi Xie (Advances in Civil Engineering)
An intermittent heating mode combining air-source heat pumps and radiators (ASHP-R) was proposed to meet the time-sharing heating demand of office workers’ residential buildings in hot summer and cold winter zones. Taking Hefei City as an example, the heating performance of the ASHP-R system under intermittent operation was experimentally studied from January 18 to 21, 2017. Based on the data on a typical day (January 19), the variation characteristics of thermal parameters and thermal comfort of heating rooms were analyzed, and the economic and environmental benefits of the ASHP-R system were evaluated. The results show that the water supply temperature of 60°C at the startup stage can rapidly increase the indoor air temperature; in the stable stage, the water supply temperature is 40°C, the indoor air maintains a suitable temperature and relative humidity, and the indoor thermal environment is basically unaffected by the change in outdoor temperature and humidity; the inner surface temperature of the envelope (except the window) presents a similar trend to the indoor air temperature, which reduces the asymmetry of the thermal radiation field around the human body. The air temperature distribution in the human activity area is uniform, and the indoor PMV is in an acceptable, comfortable, and satisfactory state; compared with all-day continuous heating with an air-source heat pump, the expense can be saved by 24.4% (by 21.5 yuan/m2) in each heating season, and the system can reduce the emissions of CO2, SO2, and NOX by 988, 29.73, and 14.86 kg/year, respectively. Therefore, the system exhibits good environmental performance and economic performance.